PENYELESAIAN SENGKETA HADHANAH MENURUT PESPEKTIF FIQIH DAN KOMPILASI HUKUM ISLAM - MUSTIKA INDAH PURNAMA SARI (PREMISE LAW JURNAL, 2015)
A divorce causes various legal consequences on husband and wife, including their children, related to hadhanah (child custody) after a divorce occurs. The resolution must be made, either by following the fiqih perspective or by following the Compilation of Islamic Law (KHI). The problem which arises in the resolution of dispute in hadhanah is which one has the right to take care of the children before the decision who will be give the custody of the children is made, how about the resolution of hadhanah according to fiqih perspective and to the Compilation of Islamic Law, and how about the right and obligation of the parent whose right to obtain hadhanah is lost.The party who will take care of the children before the decision of who will be given the custody of the children has not yet been made is the mother. This is in line with the rank for the person who has the right to be given the custody, let alone if they are still before mummayiz (Article 105 of the Civil Code). The resolution of hadhanah from the fiqih perspective can be made with two alternatives: I) by making peaceful resolution (al-ishlah or shulh), using at-tahkim method outside the Court, 2) through Islamic Judicature Body. The parent who is not given hadhanah right such as the right to see or to visit the children, the right to be respected, the right to be wall nikah (if the child is female), and the right to be the heir of the children; while his obligation toward the children is, among others, the obligation to allowance to the children (if the mother who is given the custody) and give love and affection to the children